DYSPHEMISM IN ONLINE NEWS HEADLINES: STUDENT DEMONSTRATIONS - Laili Etika Rahmawati , Wiwik Ariesta (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to describe the form of dysphemism in online news headlines of student demonstrations. The method used in this research is descriptive method with qualitative approach. Data collection techniques used are reading and note-taking technique. Data analysis was conducted by grouping data (student demonstrations), synchronizing identical data and distinguishing different data (classification into dysphemism) and eliminating similar but different data (based on the form of words, phrases, sentences or expressions). The data in this study were online news headlines of student demonstrations concerning 2019 Criminal Code Bill and Corruption Eradication Commission (KPK) for September-October 2019 period. The results indicate that the online news headlines of student demonstrations related to the Criminal Code Bill and KPK from September to October 2019 period consisting 10 data obtained dysphemism at the level of words and phrases. The forms of dysphemism found at the word level were 12 words, including 1 noun, 10 verbs, and 1 adjective. The form of dysphemism found in phrases was 1 (idiomatic phrase).